Regulation of 1,25-dihydroxyvitamin D3 receptor gene expression by 1,25-dihydroxyvitamin D3 in the parathyroid in vivo. - Naveh-Many, T (1990)
1,25-Dihydroxyvitamin D3 (1,25(OH)2D3 dramatically decreases parathyroid hormone (PTH) gene transcription. We have now studied the effect of 1,25(OH)2D3 on the 1,25(OH)2D receptor (VDR) in the parathyroid in vivo. Rats were injected with 1,25(OH)2D3 and the parathyroid-thyroid tissue analyzed for PTHmRNA and VDRmRNA. 1,25(OH)2D3 (50 and 100 pmol ip) decreased PTHmRNA at 6 h with a maximum at 48 h (less than 4% of basal), whereas VDRmRNA was increased only after 6 h with a 1.7-fold increase at 24 h. VDRmRNA levels peaked at 25 pmol 1,25(OH)2D3 with a twofold increase. Serum calcium did not affect VDRmRNA. Parathyroid VDRmRNA ran at 2.2 and 4.4 kb, whereas duodenum VDRmRNA had a single band, all of which increased after 1,25(OH)2D3. Weanling rats on a vitamin D-deficient diet for 3 wk had a more intense 2.2-kb transcript, whereas vitamin D-replete rats had a more intense 4.4-kb band. Dispersed parathyroid-thyroid cells were separated by a flow cytometry (FACS) into a parathyroid cell peak containing PTHmRNA and a second peak with cells positive for thyro-globulin mRNA and calcitonin mRNA. VDRmRNA was concentrated in the parathyroid cell peak. In situ hybridization of parathyroid-thyroid and duodenum for VDRmRNA showed its localization to the parathyroid cells and the duodenal mucosa. Therefore, the VDRmRNA in the parathyroid-thyroid tissue represents predominantly parathyroid cell and not C-cell VDRmRNA which is also a 1,25(OH)2D3 target organ. The increased VDR gene expression in the parathyroid cell would amplify the effect of 1,25(OH)2D3 to decrease PTH gene transcription.